Proceedings of the the 15th International Conference on Interaction Design and Children 2016
DOI: 10.1145/2930674.2930682
|View full text |Cite
|
Sign up to set email alerts
|

Gestures by Children and Adults on Touch Tables and Touch Walls in a Public Science Center

Abstract: Research on children's interactions with touchscreen devices has examined small and large screens and compared interaction to adults or among children of different ages. Little work has explicitly compared interaction on different platforms, however. Large touchscreen displays can be deployed flat, as in a table, or vertically, as on a wall. While these two form factors have been studied, it is not known what differences may exist between them. We present a study of visitors to a science museum, including chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Although multi-touch spherical displays have not yet been studied for educational purposes, my research takes inspiration from related work on educational flatscreen tabletop displays. Several studies focusing on science learning with flatscreen tabletops have established that touch interactions play a vital role in supporting group learning in both formal and informal learning settings [1,11]. Shaer et al [11] explored tabletop interactions for classroom science learning and found that allowing groups to spatially manipulate and annotate the learning content using intuitive gestures supported group reflection during collaborative learning.…”
Section: Multi-touch Gesture Interactive Flatscreen Displays For Learmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multi-touch spherical displays have not yet been studied for educational purposes, my research takes inspiration from related work on educational flatscreen tabletop displays. Several studies focusing on science learning with flatscreen tabletops have established that touch interactions play a vital role in supporting group learning in both formal and informal learning settings [1,11]. Shaer et al [11] explored tabletop interactions for classroom science learning and found that allowing groups to spatially manipulate and annotate the learning content using intuitive gestures supported group reflection during collaborative learning.…”
Section: Multi-touch Gesture Interactive Flatscreen Displays For Learmentioning
confidence: 99%
“…Other prior work has explored the role gestural interactions play in affording engagement around tabletop displays, without considering learning. In one of my thesis advisor's prior work, Anthony et al [1] conducted an observational study in a science museum and highlighted design implications for gestural interactions in the context of large flatscreen displays in public. For example, they recommend that designing simple gestural interactions would ensure that users are able to get engaged in science inquiry more quickly.…”
Section: Multi-touch Gesture Interactive Flatscreen Displays For Learmentioning
confidence: 99%
“…Several studies on human–computer interaction now focus on studying the finger and hand gestures (straight-swipe, arc-swipe, pinch-in, pinch-out, single-tap, multiple-tap, point-to-screen, rotate, above-the-surface and others) of those using large touchscreen displays such as tabletops or smart walls, and some are (accidentally) devoted to cartography. Anthony et al (2016) studied how children and adults interact differently with Google Earth on touch tables and touch walls in a public science centre. Hare et al (2013) investigated group interactions with the shared space of maps displayed on an interactive tabletop, and Zadow et al (2011) studied the interaction with public multi-touch, multi-user GIS systems that were installed in an exhibition.…”
Section: Map Encounters Haptic Cartographies: a Possible Agendamentioning
confidence: 99%
“…Children have not been entirely neglected in earlier public display research, but research has been limited. Children's use of these systems have been studied in museums [60], parks [61], schools [62] [63][64] and on playgrounds [65]. Several studies around pervasive and public displays have concentrated on learning [22] and behaviour change [65] [62].…”
Section: Children and Public Displaysmentioning
confidence: 99%